2021
DOI: 10.22219/cognicia.v9i2.18265
|View full text |Cite
|
Sign up to set email alerts
|

Peran mediasi self-efficacy pada work engagement dan perceived organizational support

Abstract: Excellent human resources in the organization are seen as the principal capital for the company to improve the company’s role, function, and competitiveness in facing developments and changes both internally and externally. Companies with high-stress levels need superior employees that motivated, passionate about work and loyal to the organization. These needs can refer to the characteristics of employees who are engaged with their work. However, there are still many dynamics of psychological constructs that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Attention to employee welfare is also organizational support that can increase employee self-efficacy and ultimately increase employee willingness to work (Mete, et al, 2014). Andriany & Meiyanto (2021) found that employees who work in a work environment where the company values contributions and cares about the welfare of its employees will increase self-efficacy employee. In addition, the findings of Purwaningtyas & Septyarini (2021) show that high self-efficacy has an impact on high employee work involvement.…”
Section: B Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention to employee welfare is also organizational support that can increase employee self-efficacy and ultimately increase employee willingness to work (Mete, et al, 2014). Andriany & Meiyanto (2021) found that employees who work in a work environment where the company values contributions and cares about the welfare of its employees will increase self-efficacy employee. In addition, the findings of Purwaningtyas & Septyarini (2021) show that high self-efficacy has an impact on high employee work involvement.…”
Section: B Discussionmentioning
confidence: 99%
“…Organizational support was an employee's perception of how much the organization has valued employee contributions and organizational concern for employee conditions and needs (Chiang & Hsieh, 2012). The teachers who believe that the organization values their contributions and cares about their well-being tend to reciprocate by doing good work and assignments (Andriany & Meiyanto, 2021). Teachers who feel cared for and valued by the institution will tend to feel more satisfied and more committed to their work.…”
mentioning
confidence: 99%
See 1 more Smart Citation